Molecular dynamics simulation of the tool geometry effect on nanowire formation behavior during nanoskiving - Fang, Zhuo; Yan, Yongda; Li, Zihan; Zhang, Aoxiang; Geng, Yanquan (Materials & design, 2023)
[Display omitted] •Polycrystalline Au nanowire formation mechanism under tool geometry is studied.•Large rake angles and small tool radii mean smaller nanowire thickness deviations.•Nanowires formation mechanism changes with varying tool morphology.•Microstructure evolution is sensitive to changing of tool geometry. Au nanowires have been promoted in flexible electronics, micro-nano bioelectrodes, and micro-electrochemical detection benefit from their inherent size effect, unique chemical stability, and biocompatibility. Nanoskiving methodology has been confirmed as a feasible approach to preparing multidimensional nanostructures simply and efficiently utilizing ultramicrotome. However, the morphology, dimension, and microstructure of the nanowires will be altered by the tool geometry under extrusion and shearing during the nanoskiving process. Herein, a molecular dynamics simulation and experiments of cutting polycrystalline Au utilizing nanoskiving were performed, and the nanowire formation behavior caused by the variation of the tool geometry was analyzed. Smaller rake angle and larger tool cutting edge radius favor thicker chip thickness, larger high-stress areas, increased machining forces, as well as a shift in cutting formation mechanism from shear to extrusion shear. The reduction in the clearance angle only increases the high-stress areas and machining forces. The stress state and dislocation density within the chip and plastic deformation zone were closely related to the tool topography. The conclusions provide a thorough technical analysis of the mechanism of polycrystalline Au nanowire formation as well as theoretical guidance for the design and selection of tools for nanoskiving processes.